Effect of Exercise Rehabilitation Training on Humoral Factors in Patients with Chronic Heart Failure and its Effect Observation - Yi DING; Chenchen GUO; Jinglong SUN; Wanhong WANG; Wangjun HOU; He ZHUANG (康复学报)
Objective:To examine the effects of exercise rehabilitation training on chronic heart failure (CHF) and superoxide dismutase (SOD), homocysteine (Hcy), angiotensinⅡ(AngⅡ), lactic acid (LA) and the effect of brain natriuretic peptide (BNP), providing evidence-based medical evidence for the clinical treatment of CHF.Methods:A total of 76 patients with CHF were divided into control group and combination group, with 38 patients in each group, using the random number table method. The control group received routine drug therapy; the combination group received exercise rehabilitation training in addition of the control group treatment. The effective rate and the changes of various humoral factors were observed before and after treatment.Results:The total effective rate was 89.47%in the combination group while 73.68%in the control group. The total effective rate in the combination group was better than that in the control group (P< 0.05). There was no significant difference in the distribution of cardiac function grades between the two groups before treatment (P> 0.05). The distribution of cardiac function grades in the combination group was better than that of the control group, and the difference was statistically significant (P< 0.05) after treatment. Both groups of patients before treatment the serum Ang-Ⅱ, SOD, Hcy, LA and BNP levels comparison, there were no statistically significant differences (P> 0.05); After treatment in patients with serum Ang-Ⅱ, Hcy, LA and BNP levels decreased significantly, the level of SOD increased obviously, the differences were statistically significant (P< 0.05). In the combination group after the treatment, the patient's serum of Ang-Ⅱ, Hcy, LA and BNP levels decreased, compared with the control group, the differences were statistically significant (P< 0.05), the patient's level of SOD increased in the combination group, and was better than that of the control group, the difference was statistically significant (P< 0.05).Conclusion:Compared with drug therapy alone, combined exercise rehabilitation training on the basis of conventional drug therapy can regulate relevant humoral factors more effectively, affect the vascular endothelial function of CHF patients to a certain extent, reduce the content of LA, enhance cardiac function, with positive curative effect, and it is worthy of clinical application.